Por que você não coleciona selos como todo mundo? Velhice e objetos de coleção na trajetória de Urbano, O Aposentado - Leila Beatriz Ribeiro (Ciências Sociais Unisinos)
On the basis of the "Urbano" strips, this article discusses the collections of "useless" objects in a context of heritage and social memory. In the various collections of "useless things", the memories evoked by the objects - many of them biographical - are mirror specular and subjective relations to the re-ordered world of "Urbano". They are transformed into possibilities of power and experience of a renewed life for himself and for the group around him. Travelling to places through postcards; sharing with the living statue on the square the songs from his collection of music boxes, etc. are ways of narrowing, of affirmation of an identity and of "a peaceful impression of continuity". This impression is reinforced by the "company of the things that become old together with us", according to Bosi (2009, p. 441), since the collection has the power to represent the individual, making the object to be perpetuated as a link between the individual and the world around him. Under the informational perspective, these representations provide ways of reading within a larger picture of the Brazilian society, viz. the retired elderly. Why should we not see the collectionist practice of "Urbano" as a metaphor of resistance to disposal, as a criticism of consumer attitudes, of the death of things? If old age and retired people are social categories, why should we not relate "Urbano's" objects, subject to disposal, with some representations of old age and of retired people as unproductive?